Profits and wages in Ireland, 1987-1996 - Lane, Philip R. (Statistical and Social Inquiry Society of Ireland, 1998)
A striking feature of the Irish economic resurgence since 1987 has been a major factor income shift away from labour and towards capital. (The profit share has increased from 25.1 per cent in 1987 to 34.8 per cent in 1996.) In this paper, we examine the role of the national strategy of wage moderation in explaining this shift, consider its potential benefits and ask whether it is sustainable. We highlight the critical role of fiscal policy in minimising the trade-off between the returns to capital and labour. Finally, imminent membership of a European Monetary Union makes it all the more important not to overshoot the equilibrium rate of wage growth for the Irish economy.
Barrington Lecture 1997/1998
Read before the Society, 7 May 1998
Keywords: Profits; Wages; Irish economy; Irish labour markets; 314.15